Literature, modernism and myth : belief and responsibility in the twentieth century - Bell, Michael, 1941- (Cambridge University Press, 1997)
The use of myth in Modernist literature is a misleadingly familiar theme. Joyce's appropriation of Homer's Odyssey and Eliot's of Frazer's Golden Bough are, like Lawrence's primitivism or Yeats's nationalist folklore, attempts to discover an underlying metaphysic in an increasingly fragmented world. In Literature, Modernism and Myth Michael Bell also examines the relationship of myth and modernism to postmodernism. Myth, Bell shows, is inherently flexible; it was used to justify Pound's totalizing vision of society which eventually descended into fascism, and the liberal, ironic vision of human existence Joyce and Mann expressed. Those theorists who present myth as another form of mystification, a search for false origins, ignore its use by modernists to emphasise the ultimate contingency of all values. This anti-foundational element, Bell claims, enables myth to act as a corrective to the claims of ideological critique. Bell shows how postmodern concerns with political and social responsibility, and the role literature plays in formulating this, have in fact been inherited from modernism.